Non verba, sed amicitia – polsko-węgierskie słowa Feliksa Netza - Kadłubek, Zbigniew (Postscriptum Polonistyczne, 2020)
It is an obituary notice of Feliks Netz, a great translator from the Hungarian language, a writer, a poet, an art of words admirer. The author of the obituary refers to the translation works of Feliks Netz and deliberates on the art of translation itself and a special friendship between an author and a translator, which appears to be impossible to describe with words.